Sugar Price Policy and Indonesia’s Trade Balance - PUDJIASTUTI, Agnes Quartina; KEMBAUW, Esther (Journal of Advanced Research in Law and Economics, 2018)
Sugar price policy always directed at conditions in which supply is equal to demand. This study aimed to evaluate the impact of increase in sugar prices on Indonesia’s trade balance. Evaluation was done by using Tables I-O and SAM Indonesia in 2008 to developed Computable General Equilibrium (CGE) model. Indonesian economy were aggregated into 23 sectors with 8 households and 3 primary input. An increase in sugar prices of Indonesia have an impact on domestic output, exports, imports and trade balance. In agricultural sector, domestic output and imports increased, exports dropped, but Indonesian trade balance was still surplus. While the industrial and service sectors, domestic output and exports dropped, as well as imports increased, but the trade balance was deficit. Sugar imports even increased by 9.09%. It needs to watch out by the government because it could lead to a deficit in the trade balance.